PERJANJIAN KERJASAMA WARALABA, ANTARA PT. RAOS ANEKA PANGAN DENGAN NY. HJ. MARYENIK YANDA, SH. - lhamdi *; Rahmad Hendra; Riska Fitriani (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2014)
ABSTRAKThe franchice agreement has distinctive characteristics of this form of agreement in general. Clause franchise agreements generaly even been determined by government regulation number 42 of 2007 on franchise.To ensure legal certainty in the franchise business franchisor and franchisee always make the franchise agreement. The franchise agreement is a very important position in the franchise business, to get a Franchise Registration Certificate. The purpose of this thesis to determine the rights and obligations of the franchisor and the franchisee in a franchise business execution raos noodles and to investigate the problems and constraints to the implementation of the franchise raos noodles under the franchise agreement, between PT. Raos Aneka Pangan with Ny. Hj. Maryenik Yanda, SH. This type of research is empirical juridical research. Empirical legal research is primarily a study of the laws of nature describe or depict a conflict between the law in books and law in actions. The data source used is the primary law, secondary and tertiary. From the results of this study concluded, the rights and obligations in the execution of the franchise agreement, is required to be made in the content of the franchise agreement as mandated by Article 5 of Government Regulation No. 42 Year 2007 on Franchising. While the problems and obstacles that a lack of attention in fostering business Franchisor Franchisee Franchisee thus can be considered to run his own business.Keywords: Franchise Agreement, Franchisee And Franchisor.